The Optical Properties and Photo catalytic Activity of ZnS-TiO2/Graphite Under Ultra Violet and Visible Light Radiation - Fitria Rahmawati; Rini Wulandari; Irvina M. Murni; Moedjijono Moedjijono (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
This paper discuss research about the optical properties and photo catalytic activity of TiO2 film on graphite substrate and its modification with ZnS. The optical properties investigated are the light response at various light wavelength and the gap energy (Eg). Meanwhile, the photocatalytic activity was studied from isopropanol degradation to determine the Quantum Yield, QY and kinetics of reaction. The results show that the TiO2 layer is consisted of rutile and anatase phases. Meanwhile, the ZnS peaks are at 2θ of 27.91o and 54.58o. The gap energy of TiO2/G consist of two band gap representing the band gap of rutile and anatase. The ZnS deposition shifted the band gap into single gap of 3.40 eV which is in between the gap energy of single TiO2 and single ZnS. The isopropanol degradation with TiO2/G photocatalyst under visible light radiation did not produce any new peaks representing product. Meanwhile, the photocatalytic process under 380 nm light produce new peaks representing the electronic transition of acetone. The isopropanol degradation with ZnS-TiO2/Graphite produced new peaks that indicates the photocataytic activity of ZnS-TiO2/Graphite whether under UV or visible light radiation. The siginificant role of ZnS also proven by the increase of QY values and the increase of rate constant, k. Copyright © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).